Comparison of nutritional supplements in improving glycolipid metabolism and endocrine function in polycystic ovary syndrome: a systematic review and network meta-analysis - Hu,Xinyin; Wang,Wanyi; Su,Xuhan; Peng,Haoye; Tan,Zuolin; Li,Yunqing; Huang,Yuhua (PeerJ, 2023)
Objective To explore the comparative effectiveness of nutritional supplements in improving glycolipid metabolism and endocrine function in patients with polycystic ovary syndrome (PCOS). Method Randomized controlled clinical trials on the effects of nutritional supplements in PCOS patients were searched in PubMed, Embase, Cochrane Library, and Web of Science from their establishments to March 15, 2023. Then, literature screening, data extraction, and network meta-analysis were performed. This study was registered at PROSPERO (registration number CRD 42023441257). Result Forty-one articles involving 2,362 patients were included in this study. The network meta-analysis showed that carnitine, inositol, and probiotics reduced body weight and body mass index (BMI) compared to placebo, and carnitine outperformed the other supplements (SUCRAs: 96.04%, 97.73%, respectively). Omega-3 lowered fasting blood glucose (FBG) (SUCRAs: 93.53%), and chromium reduced fasting insulin (FINS) (SUCRAs: 72.90%); both were superior to placebo in improving insulin resistance index (HOMA-IR), and chromium was more effective than Omega-3 (SUCRAs: 79.99%). Selenium was potent in raising the quantitative insulin sensitivity index (QUICKI) (SUCRAs: 87.92%). Coenzyme Q10 was the most effective in reducing triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels (SUCRAs: 87.71%, 98.78%, and 98.70%, respectively). Chromium and probiotics decreased TG levels, while chromium and vitamin D decreased TC levels. No significant differences were observed in high-density lipoprotein cholesterol (HDL-C), total testosterone (TT), sex-hormone binding globulin (SHBG), and C-reactive protein (CRP) between nutritional supplements and placebo. Conclusion Carnitine was relatively effective in reducing body mass, while chromium, Omega-3, and selenium were beneficial for improving glucose metabolism. Meanwhile, coenzyme Q10 was more efficacious for improving lipid metabolism. However, publication bias may exist, and more high-quality clinical randomized controlled trials are needed.
Keywords: Nutritional supplements; Polycystic ovary syndrome; Network meta-analysis; Endocrine function; Glycolipid metabolism